Knowledge gaps and predictors of early urinary tract infections detection by nurses in the aged population - Marino, Aline Garbo; Menezes, João Daniel de Souza; Silva, Matheus Querino da; Aleixo, Daniele Nunes Longhi; Santos, Emerson Roberto dos; Ribeiro, Renato Mendonça; Parro, Maria Claudia; Lima, Alba Regina de Abreu; Caldas, Heloisa Cristina; Brienze, Vania Maria Sabadoto; André, Júlio César; Ribeiro, Rita de Cássia Helu Mendonça (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Urinary tract infection (UTI) is a frequent cause of morbidity and mortality in hospitalized elderly patients. Early detection of signs and symptoms by nurses is crucial for timely diagnosis and treatment. This study aimed to verify if nurses detect early the signs and symptoms of UTI in the elderly in hospital units. Methods: An observational, cross-sectional study with a descriptive design and quantitative approach was conducted in a teaching hospital and a private hospital in northwestern São Paulo. Data were collected from August to November 2019 through individual interviews with 102 nurses using a validated questionnaire. Results: The majority of nurses (93.14%) judged having sufficient knowledge in urological diseases. Those with time since graduation of ten years or more and professional experience of five years or more demonstrated knowledge above satisfactory in the early identification of UTI signs and symptoms in the elderly. Nurses in the intensive care unit had higher rates of correct answers regarding the concept of elderly according to WHO (p=0.037), diaper use increasing UTI risk (p=0.000), and UTI being more common in females (p=0.026). Fever was recognized by 84.31% as a sign not always present in UTI in the elderly. Conclusion: Nurses detected early the signs and symptoms of UTI in the elderly in hospital units, especially those with longer time since graduation and professional experience. Periodic assessment of professionals’ knowledge is important, and nurses must be updated and trained to conduct training with their team, aiming to provide excellent and evidence-based care.